Annual athletic training completion stage prior to 2021 Paralympic games - Vorobiev, S. A.; Baryaev, A. A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze benefits of the individual-diagnosis-specific pre- Paralympic Games annual training cycle completion stage.